The Arithmetic-Geometric-Harmonic Mean

Calculus Level 5

Let us try to devise a new mean that combines the arithmetic mean, geometric mean, and harmonic mean, called the arithmetic-geometric-harmonic mean.

Given two positive real numbers x , y x,y , define AM ( x , y ) = a 1 = x + y 2 , GM ( x , y ) = g 1 = x y , HM ( x , y ) = h 1 = 2 1 x + 1 y \text{AM}(x,y)=a_1=\frac{x+y}{2},\text{GM}(x,y)=g_1=\sqrt{xy},\text{HM}(x,y)=h_1=\frac{2}{\frac{1}{x}+\frac{1}{y}} . In addition, for n > 1 n>1 , a n = a n 1 + g n 1 + h n 1 3 g n = a n 1 g n 1 h n 1 3 h n = 3 1 a n 1 + 1 g n 1 + 1 h n 1 . \begin{aligned} a_n&=\frac{a_{n-1}+g_{n-1}+h_{n-1}}{3}\\ g_n&=\sqrt[3]{a_{n-1}g_{n-1}h_{n-1}}\\ h_n&=\frac{3}{\frac{1}{a_{n-1}}+\frac{1}{g_{n-1}}+\frac{1}{h_{n-1}}}. \end{aligned} Then, the arithmetic-geometric-harmonic mean AGHM ( x , y ) = lim n a n = lim n g n = lim n h n \text{AGHM}(x,y)=\displaystyle\lim_{n\to\infty}a_n=\lim_{n\to\infty}g_n=\lim_{n\to\infty}h_n .

Using the AM-GM-HM inequality , it is obvious that for two given positive real numbers x , y x,y where x y x\ne y , if the arithmetic-geometric-harmonic mean exists, HM ( x , y ) < AGHM ( x , y ) < AM ( x , y ) \text{HM}(x,y)<\text{AGHM}(x,y)<\text{AM}(x,y) . But how does AGHM ( x , y ) \text{AGHM}(x,y) compare with GM ( x , y ) ? \text{GM}(x,y)?

AGHM ( x , y ) > GM ( x , y ) \text{AGHM}(x,y)>\text{GM}(x,y) AGHM ( x , y ) < GM ( x , y ) \text{AGHM}(x,y)<\text{GM}(x,y) AGHM ( x , y ) = GM ( x , y ) \text{AGHM}(x,y)=\text{GM}(x,y) Depends on x x and y y AGHM ( x , y ) \text{AGHM}(x,y) does not exist for all positive reals x , y x,y where x y x\ne y

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
May 21, 2018

Write g = G M ( x , y ) g = GM(x,y) . Then g 1 = g g_1 = g and a 1 h 1 = g 2 a_1h_1 = g^2 . Suppose n N n \in \mathbb{N} and that g n = g g_n = g and a n h n = g 2 a_nh_n = g^2 . Then a n + 1 = 1 3 ( a n + g + h n ) g n + 1 = a n × g × h n 3 = g h n + 1 = 3 a n g h n a n g + a n h n + g h n = 3 g 3 g ( a n + g + h n ) = 3 g 2 a n + g + h n \begin{aligned} a_{n+1} & =\; \tfrac13(a_n + g + h_n) \\ g_{n+1} & = \; \sqrt[3]{a_n \times g \times h_n} \; = \; g \\ h_{n+1} & = \; \frac{3a_ngh_n}{a_ng + a_nh_n + gh_n} \; = \; \frac{3g^3}{g(a_n + g + h_n)} \; = \; \frac{3g^2}{a_n + g + h_n} \end{aligned} so that g n + 1 = g g_{n+1} = g and a n + 1 h n + 1 = g 2 a_{n+1}h_{n+1} = g^2 .

Thus we deduce that g n = g g_n = g and that a n h n = g 2 a_nh_n = g^2 for all n 1 n \ge 1 . Now we know that a n > g n = g a_n > g_n = g for all n n . Moreover a n a n + 1 = 1 3 ( 2 a n g h n ) = 1 3 ( 2 a n g g 2 a n ) = 1 3 a n ( a n g ) ( 2 a n + g ) > 0 a_n - a_{n+1} \; = \; \tfrac13(2a_n - g - h_n) \; = \; \tfrac13\big(2a_n - g - \tfrac{g^2}{a_n}\big) \; = \; \tfrac{1}{3a_n}(a_n - g)(2a_n + g) \; > \; 0 so we know that ( a n ) (a_n) is a decreasing sequence, and hence converges to some α g \alpha \ge g . Since a n + 1 = 1 3 ( a n + g + g 2 a n ) a_{n+1} \; = \; \tfrac13\big(a_n + g + \tfrac{g^2}{a_n}\big) we deduce that α = 1 3 ( α + g + g 2 α ) \alpha \; =\; \tfrac13\big(\alpha + g + \tfrac{g^2}{\alpha}\big) which implies that 2 α 2 g α g 2 = 0 2\alpha^2 - g\alpha- g^2 = 0 and hence, since α g \alpha \ge g , that α = g \alpha = g . Thus lim n a n = g \lim_{n \to \infty}a_n = g . Since h n = g 2 a n h_n = \tfrac{g^2}{a_n} , we deduce that lim n h n = g \lim_{n\to\infty}h_n = g as well. Thus we deduce that A G H M ( x , y ) = g = G M ( x , y ) AGHM(x,y) = g = GM(x,y) .

It is worth noting that a n + 1 g = 1 3 a n ( a n g ) 2 a_{n+1} - g \; = \; \tfrac{1}{3a_n}(a_n - g)^2 and so the rate of convergence of a n a_n to g g is quadratic.

Nick Turtle
May 20, 2018

Note : This is not a full solution, but more of an outline on how one can obtain the solution.

This question was inspired after reading up on the arithmetic-geometric mean and the geometric-harmonic mean (both really interesting means, by the way).

Let us first prove that AGHM ( x , y ) \text{AGHM}(x,y) exists for all positive reals x , y x,y . Without loss of generality, assume x y x\le y .

Denote a = lim n a n , g = lim n g n , h = lim n h n a=\displaystyle\lim_{n\to\infty}a_n,g=\displaystyle\lim_{n\to\infty}g_n,h=\displaystyle\lim_{n\to\infty}h_n . Since a n + 1 a n a_{n+1}\le a_{n} and h n + 1 h n h_{n+1}\ge h_{n} for all n 1 n\ge 1 and both a n , h n a_n,h_n are bounded, a a and h h both exist. (We're going to show later that g n = g n + 1 g_n=g_{n+1} for all n n and thus g g also exists.)

Note that by the AM-GM-HM inequality, h g a h\le g\le a . We know that 3 a n = a n 1 + g n 1 + h n 1 3a_n=a_{n-1}+g_{n-1}+h_{n-1} . Take n n\to\infty to get the result that 2 a = g + h 2a=g+h . Since a g h a\ge g\ge h , this necessarily means that a = g = h a=g=h . Thus, AGHM ( x , y ) \text{AGHM}(x,y) exists.

Now, it's easy to show that a 1 h 1 = g 1 2 a_1h_1=g_1^2 . Then, assuming that a n h n = g n 2 a_nh_n=g_n^2 for some n n , one can also show that a n + 1 h n + 1 = g n + 1 2 a_{n+1}h_{n+1}=g_{n+1}^2 . Knowing that a n h n = g n 2 a_nh_n=g_n^2 for all n 1 n\ge 1 , it is easy to demonstrate that a n h n = a n + 1 h n + 1 a_nh_n=a_{n+1}h_{n+1} and thus g n = g n + 1 g_{n}=g_{n+1} for all n 1 n\ge 1 .

Thus, AGHM ( x , y ) = GM ( x , y ) \text{AGHM}(x,y)=\text{GM}(x,y) .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...